“I,” “Unknown”: Female Subjectivity in Miriam Waddington’s Early Life Writing and Green World (1945) - McLauchlan, Laura (Canadian Jewish Studies / Études juives canadiennes, 2003)
This essay examines the early life writing and poetry of MiriamWaddington with the goal of contributing to a reevaluation ofsecond wave Canadian modernism. More specifically, it usesjournals, unpublished poems, and Waddington’s Master’s thesis(in Social Work) as a means of contextualizing the “innerunderground life” of a writer who is both Jewish and female. Indoing so, this essay has two purposes: the first is to offer anaccount of the material relevant to this study found in the early unpublished material in the Waddington Papers held in Libraryand Archives Canada, and second, to explore female subjectivityin both the unpublished life writing and in Green World.